2018
DOI: 10.1192/bjp.2018.264
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse and psychotic experiences in adulthood: findings from a 35-year longitudinal study

Abstract: BackgroundThe extent to which exposure to childhood sexual and physical abuse increases the risk of psychotic experiences in adulthood is currently unclear.AimsTo examine the relationship between childhood sexual and physical abuse and psychotic experiences in adulthood taking into account potential confounding and time-dynamic covariate factors.MethodData were from a cohort of 1265 participants studied from birth to 35 years. At ages 18 and 21, cohort members were questioned about childhood sexual and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 25 publications
4
37
1
Order By: Relevance
“…As interesting ndings of our study, the summary of regression analysis results revealed that for the patients with schizophrenia spectrum and other psychotic disorders, positive symptoms were related to sexual abuse, dissociative amnesia, absorption, and physical abuse, negative symptoms were associated with physical abuse, and general psychopathology symptoms were related to absorption and physical abuse. These ndings were consistent with studies conducted by She eld et al [13], Bendall et al [14], and Read et al [15], whereas they were inconsistent with results obtained by Bell et al [16]. However, contrary to She eld et al [13], we observed no relationship between emotional abuse and psychotic symptoms.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…As interesting ndings of our study, the summary of regression analysis results revealed that for the patients with schizophrenia spectrum and other psychotic disorders, positive symptoms were related to sexual abuse, dissociative amnesia, absorption, and physical abuse, negative symptoms were associated with physical abuse, and general psychopathology symptoms were related to absorption and physical abuse. These ndings were consistent with studies conducted by She eld et al [13], Bendall et al [14], and Read et al [15], whereas they were inconsistent with results obtained by Bell et al [16]. However, contrary to She eld et al [13], we observed no relationship between emotional abuse and psychotic symptoms.…”
Section: Discussionsupporting
confidence: 71%
“…They also suggested the marked relationship between delusions and childhood physical abuse, contrary to the results obtained by Bell et al [16].…”
Section: Introductionmentioning
confidence: 64%
“…Importantly, effects were not better accounted for by concurrent cannabis use, even though this may confer an additional risk [29]. However, not all premorbid risk factors for psychosis have been controlled for in these studies (e.g., familial risk [83], trauma [84], perinatal factors, immigration and urbanicity [85]) and future studies should control for these factors.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the unadjusted estimates we have presented are likely to be inflated due to the multitude of risk factors for poor mental health that co-occur with the use of amphetamines. Possible aetiological factors contributing to high rates of mental disorders amongst people who use amphetamines include common risk factors for substance use problems and mental disorders (e.g., familial risk [82], early childhood trauma [84]), the pharmacological effects of amphetamines (e.g., mood enhancement, withdrawal symptoms), the lasting neurophysiological and potential neurocognitive sequelae of chronic heavy use [88], as well as the secondary consequences of substance dependence (e.g., social isolation related to unemployment, stigma) and co-occurring risk factors (e.g., high rates of polysubstance use and low socio-economic background [87]).…”
Section: Discussionmentioning
confidence: 99%
“…These theories were elaborated by Ferenczi 2 , who suggested that childhood sexual abuse could give rise to psychotic symptoms in adults. Following these early conceptualizations, and notwithstanding unmeasured confounds, consistent observational evidence indicates that people who experience DT have a higher risk of psychosis in later life [3][4][5][6][7] .…”
mentioning
confidence: 83%